Synthesis, structure, and magnetic properties of n=2 Ruddlesden-Popper manganates - Battle, P; Rosseinsky, M (1999)
Low-field magnetoresistance is observed both below and above the three-dimensional Curie temperature of the intrinsically layered Ruddlesden-Popper manganates Sr2-xLa1+xMn2O7. Significant differences from the more extensively investigated n=∞ three-dimensional perovskites include a much more rapid suppression of ferromagnetic ordering as the size of the lanthanide cation is reduced and more complex magnetic and structural behaviour in the manganese oxidation state range which produces charge ordering in the n=1 and n=∞ homologues. Control of chemical imperfections, such as intergrowth and phase co-existence, is required to allow understanding of the physical properties of this system. © Elsevier Science Ltd.